Dietary Bioactive Lipids: A Review on Absorption, Metabolism, and Health Properties - Zhang, Yan; Zhang, Tianyi; Liang, Yan; Jiang, Lianzhou; Sui, Xiaonan (Journal of agricultural and food chemistry, 2021)
Dietary lipids are an indispensable source of energy and nutrition in human life. Numerous studies have shown that dietary bioactive lipids have many health benefits, including prevention or treatment of chronic diseases. The different chemical compositions and structural characteristics of bioactive lipids not only affect their digestion, absorption, and metabolism but also affect their health properties. In this review, the major dietary bioactive lipids (fatty acids, carotenoids, phytosterols, phenolic lipids, fat-soluble vitamins, and sphingomyelins) in foods are systematically summarized, from the aspects of composition, digestion, absorption, metabolism, source, structural characteristics, and their health properties. In particular, the relationship between the compositional and structural changes of bioactive lipids and their absorption and metabolism is discussed as well as their effect on health properties. This review provides a comprehensive summary toward health properties of dietary bioactive lipids.